Analisis Butir Soal Ujian Tengah Semester Ganjil Seni Budaya Kelas VII Di SMPN 29 Sijunjung - Shanta Monica; Yos Sudarman (FBS Universitas Negeri Padang, 2019)
This article aims to describe the quality of the item about the Mid-term test of seventh-grade students of SMPN 29 Sijunjung which includes the level of difficulty, distinguishing power and the effectiveness of deception. The sample in this study was taken for 50 students’ answer sheets. The results show that the results of the analysis of the difficulty level of mid-term test of art and cultural 7th grade students of SMPN 29 Sijunjung academic year of 2018/2019 have a difficult category for 3 items (12%), items with medium categories are 14 items (56% ) and easy question categories are 8 items (32%). The item differentiation power has a bad category distinguishing power for 9 items (36%), sufficient categories for 7 items (28%), good categories for 7 items (28%), and very good categories are 2 items (8%). The effectiveness of deception of the questions from 25 items, it was found 8 items (32%) the function of the deceiver was said to be good or already functioning, while 17 items (68%) the function of the deception was not good. Joint analysis of mid-term test of art and cultural 7th grade students of SMPN 29 Sijunjung academic year of 2018/2019 at the level of difficulty, differentiating power and effectiveness of question deception, items of good quality are 5 items (20%), good enough are 6 items ( 24%), and not good (bad) are 14 items (56%).